The Influence of Digital Marketing, Service and Product Quality on Loyalty Through Satisfaction at La Moda Del Gelato Solo - Ramadhani Darius Van Djava; Henri Dwi Wahyudi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of digital marketing, service quality, and product quality on customer loyalty, with customer satisfaction as a mediating variable, at the La Moda del Gelato culinary business in Solo. The background of this research is based on the shift in young consumer behavior, who are increasingly relying on digital technology for purchasing activities, and the importance of positive experiences in shaping customer loyalty. This study used a quantitative method with a Partial Least Squares (PLS) approach using SmartPLS 3.0 software. The sample size was 200 respondents aged 15–30 who were active customers of La Moda del Gelato Solo. The results show that digital marketing, service quality, and product quality have no direct effect on loyalty, but they have a significant indirect effect through customer satisfaction as a mediating variable. Thus, customer satisfaction is proven to be a key element in fostering young customer loyalty. This research provides important implications for culinary businesses to focus more on improving service and product quality, as well as digital marketing strategies that can create satisfaction and memorable experiences for customers.